The Great Vasyugan Mire of western Siberia: Hydrochemistry and greenhouse gas dynamics of peatland pools of the world’s largest mire - Sergey N. Vorobyev; Yuri Kolesnichenko; Ivan V. Krickov; Alexander E. Berezin; Sergey N. Kirpotin; Oleg S. Pokrovsky (Ecological Indicators, 2025)
Siberian peatlands act as the primary regulator for carbon (C) exchange between land and atmosphere; however, the aquatic component of this ecosystem, peatland pools, remains virtually unknown with respect to biogeochemical parameters and C fluxes. Here we report results from a ‘snapshot’ (end of spring period) study investigating hydrochemical parameters and greenhouse gas (CO2 and CH4) concentrations and emissions from shallow peatland pools of the Great Vasyugan Mire (GVM) in western Siberia. The pools were highly oligotrophic, acidic, humic, iron-rich, poor in chloride and sulfate, and emitted 0.15 g C-CO2 m−2 d-1 as measured by floating chambers. There was significant dependence between the pool area and various hydrochemical parameters across wide range of pool sizes (from 700 to 1,380,000 m2). Concentrations of CO2, CH4, dissolved organic carbon (DOC), some organic nutrients and lithogenic trace elements increased with decreasing pool size, likely reflecting organic matter delivery from peat and shallow subsurface waters. In contrast, with increasing pool size, there was a decrease in DOC aromaticity and an increase in pH and concentration of labile elements (anions, alkaline and alkaline-earth metals). This was consistent with an increase in autochthonous production and degree of connection to groundwater reservoirs. Annual emissions of C from peatland pools and lakes of the GVM are comparable to peat growth rate in the territory and exceed the lateral export of DOC by rivers. Future studies should address the seasonal aspects of C biogeochemistry, including the ice cover period.